The guanidine thiocyanate‐high EDTA method for total microbial RNA extraction from severely heavy metal‐contaminated soils. Issue 2 (23rd June 2020) - Pei, Yaxin; Mamtimin, Tursunay; Ji, Jing; Khan, Aman; Kakade, Apurva; Zhou, Tuoyu; Yu, Zhengsheng; Zain, Hajira; Yang, Wenzhi; Ling, Zhenmin; Zhang, Wenya; Zhang, Yingmei; et al.
Summary: Molecular analyses relying on RNA, as a direct way to unravel active microbes and their functional genes, have received increasing attention from environmental researchers recently. However, extracting sufficient and high‐quality total microbial RNA from seriously heavy metal‐contaminated soils is still a challenge. In this study, the guanidine thiocyanate‐high EDTA (GTHE) method was established and optimized for recovering high quantity and quality of RNA from long‐term heavy metal‐contaminated soils. Due to the low microbial biomass in the soils, we combined multiple strong denaturants and intense mechanical lysis to break cells for increasing RNA yields. To minimize RNAase and heavy metals interference on RNA integrity, the concentrations of guanidine thiocyanate and EDTA were increased from 0.5 to 0.625 ml g −1 soil and 10 to 100 mM, respectively. This optimized GTHE method was applied to seven severely contaminated soils, and the RNA recovery efficiencies were 2.80 ~ 59.41 μg g −1 soil. The total microbial RNA of non‐Cr(VI) (NT) and Cr(VI)‐treated (CT) samples was utilized for molecular analyses. The result of qRT‐PCR demonstrated that the expressions of two tested genes, chrA and yieF, were respectively upregulated 4.12‐ and 62.43‐fold after Cr(VI) treatment. The total microbial RNA extracted from NT and CT samples, respectively, reached to 26.70 μg and 30.75 μg, which were much higher than the required amount (5 μg) for metatranscriptomic library construction. Besides, ratios of mRNA read were more than 86%, which indicated the high‐quality libraries constructed for metatranscriptomic analysis. In summary, the GTHE method is useful to study microbes of contaminated habitats. Abstract : This study developed and optimized the GTHE method for isolating high‐quality total microbial RNA from severely heavy metal‐contaminated soils. The yielded RNA by the optimized GTHE method can be used for comprehensive molecular analyses. Further, the identified RNA extraction influencing factors and the corresponding solving strategies provide an important reference to other soil total microbial RNA extraction methods.